ASIMETRI KOMUNIKASI DALAM SISTEM TENGKULAK DAN DAMPAKNYA TERHADAP PENDAPATAN PETANI JERUK LOKAL - Mahmiludin, Dede; Sukmawati, Dety; Juliana, Edang; Andita Erdayani, Yelly; Marina, Febrianti (Journal of Sustainable Agribusiness, 2025)
This study aims to analyze the forms of communication asymmetry within the local orange marketing system between farmers and middlemen, and its impact on farmers’ income in Ciampel District, Karawang Regency. The findings reveal that communication asymmetry arises from unequal access to information related to pricing, market access, and harvest assessment, with middlemen holding dominant control over information flow. Structural constraints such as limited infrastructure, low digital literacy, and socio-economic ties—particularly debt relations—further reinforce farmers’ dependence on middlemen. As a result, farmers possess weak bargaining power and often receive prices significantly lower than actual market values. The study concludes that communication asymmetry substantially suppresses farmers’ income, emphasizing the need for interventions such as strengthening farmer groups, enhancing the role of agricultural extension workers, optimizing digital information systems, and developing fairer marketing partnerships to reduce information inequality.